(untitled) (Stato, Chiese e pluralismo confessionale, 2025)
Digital education and virtuous smart collective dynamics We are now all part of an efficient and competitive economic development model which, in indulging the frenzy of technological progress and its excessive use in a trend of consumerism and waste, has proved unsustainable for the planet and for humankind, leading to environmental degradation and increasing inequality, injustice and the marginalisation of humanity. This contribution aims to counter this pernicious trend by highlighting the need to educate people in the ethical use of new technologies, spreading the principles of algorethics that are being developed thanks to the contribution of religious denominations. By promoting the fundamental values of human dignity and respect for the entire ecosystem, some religious bodies and associations, as well as other collective organisations with various ethical inspirations, use digital technologies to combine the need to protect the common good with that of ensuring the full realisation of their group identity. In fact, there are virtuous examples of smart collective dynamics, in which groups of individuals use multimedia platforms and artificial intelligence to achieve worthwhile goals such as social well-being, conscious consumption, saving, limiting waste and environmental pollution, sharing cultural heritage, reducing inequalities, socialising people through the internet, etc. SOMMARIO: 1. Introduzione - 2. L’educazione digitale per un uso eticamente plausibile delle nuove tecnologie - 3. La tecnologia smart quale medium tra individui e collettività nel perseguire il bene comune - 4. Alcuni esempi virtuoso di dinamiche collettive basate sulle piattaforme multimediali: a) le banche del cibo; b) le app per l’alimentazione religiosamente caratterizzata; c) un QR Code per il turismo esperienziale; d) l’impegno per ridurre il digital divide; e) il carpooling; f) il social lending; g) la valorizzazione digitale dei beni culturali. - 5. Conclusioni.